2022
DOI: 10.3390/diagnostics12041018
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Tumors’ Classification Using Deep-Neural-Network-Based Features with SVM Classifier

Abstract: The complexity of brain tissue requires skillful technicians and expert medical doctors to manually analyze and diagnose Glioma brain tumors using multiple Magnetic Resonance (MR) images with multiple modalities. Unfortunately, manual diagnosis suffers from its lengthy process, as well as elevated cost. With this type of cancerous disease, early detection will increase the chances of suitable medical procedures leading to either a full recovery or the prolongation of the patient’s life. This has increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The authors demonstrated that their aggregation-based deep learning model performed much better than individual state-of-the-art CNNs, with an overall accuracy of 96.58%. The authors of [ 7 ] employed deep learning for the purpose of Glioma tumors. A multiclass model was built that used deep learning techniques for feature extraction and used SVMs for the purpose of classification.…”
Section: Introductionmentioning
confidence: 99%
“…The authors demonstrated that their aggregation-based deep learning model performed much better than individual state-of-the-art CNNs, with an overall accuracy of 96.58%. The authors of [ 7 ] employed deep learning for the purpose of Glioma tumors. A multiclass model was built that used deep learning techniques for feature extraction and used SVMs for the purpose of classification.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the image processing field has been aided by Convolutional Neural Networks (CNN) [ 18 , 19 , 20 ]. An end-to-end system requiring minimal preprocessing results from the integration of the various image features and classifiers in CNN.…”
Section: Introductionmentioning
confidence: 99%
“…In the second stage, proposed techniques for the segmentation of the tumorous image were explained. In the third stage, proposed significant contributions for the classification of tumorous images into the four Glioma classes; Necrosis, Edema, Enhancing, and Non-enhancing were detailed [ 5 ].…”
Section: Introductionmentioning
confidence: 99%